Salicylic Acid Treatment Reduces Lipid Peroxidation and Chlorophyll Degradation and Preserves Quality Attributes of Pointed Gourd Fruit - Nitin Yadav; Anil K. Singh; Talha Bin Emran; Ratiram G. Chaudhary; Rohit Sharma; Swati Sharma; Kalyan Barman (Journal of Food Quality)
The marketability of pointed gourd fruit is drastically reduced after harvest due to moisture loss, chlorophyll degradation, yellowing of the skin, and shriveling. The present investigation studied the effect of exogenous salicylic acid (SA) treatment on senescence and fruit quality attributes of pointed gourd during storage under ambient conditions. Fruits were treated by immersing them in different concentrations of SA (1.0 mM, 2.0 mM, and 3.0 mM) and distilled water (control) for 5 minutes. The investigation showed beneficial effects of 3.0 mM SA treatment in lowering weight loss (16.8%), maintaining higher chlorophyll (32.8%) in the skin, and reducing lipid peroxidation (20.2%) compared to the control. SA (3.0 mM)-treated fruits retained 15.3% higher ascorbic acid and about 18% higher total phenol, flavonoids, and radical scavenging activity over pointed gourd fruits in the control group. However, significant difference in the total antioxidant capacity after 6 days of storage was not noted between SA-treated and control fruit. Thus, postharvest salicylic acid treatment can beneficially be used to extend marketability and delay quality deterioration of pointed gourd fruits stored under ambient conditions.